2017
DOI: 10.1007/s11356-017-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Apex predatory mammals as bioindicator species in environmental monitoring of elements in Dinaric Alps (Croatia)

Abstract: Tissue element investigations of apex terrestrial mammals are very scarce in Europe. We quantified 16 essential and nonessential elements in the kidney cortex, liver, and muscle tissue of 467 brown bears (Ursus arctos), 125 gray wolves (Canis lupus), one Eurasian lynx (Lynx lynx), and three golden jackals (Canis aureus) from Croatia by inductively coupled plasma mass spectrometry (ICP-MS). Renal cadmium (0.6% of animals) and lead (1%) and hepatic lead (5%) were found in toxicologically relevant levels for mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
4
14
0
Order By: Relevance
“…This result was consistent with data reported in the mongoose populations from four habitats in Japan (Horai et al 2006;Watanabe et al, 2010) In the case of humans, it is known that Cd exists mainly in the kidney (Underwood, 1975). In some terrestrial mammals (Fritsch et al, 2010;Lazarus et al, 2017), marine mammal (Watanabe et al, 1996, Capelli et al, 2008, Agusa et al, 2011Reed et al 2015, Mahfouz et al, 2014, and avian species (Nam et al, 2005;Horai et al, 2007;Zaccaroni et al, 2011;Cui et al, 2013), the Cd accumulation was more abundant in the kidney than in the other organs and tissues. Together, distribution patterns of Mn, Fe, Cu and Cd in the liver and kidney of small Indian mongoose population from Hawaii were similar to mongooses from Japan as well as other terrestrial and marine mammals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result was consistent with data reported in the mongoose populations from four habitats in Japan (Horai et al 2006;Watanabe et al, 2010) In the case of humans, it is known that Cd exists mainly in the kidney (Underwood, 1975). In some terrestrial mammals (Fritsch et al, 2010;Lazarus et al, 2017), marine mammal (Watanabe et al, 1996, Capelli et al, 2008, Agusa et al, 2011Reed et al 2015, Mahfouz et al, 2014, and avian species (Nam et al, 2005;Horai et al, 2007;Zaccaroni et al, 2011;Cui et al, 2013), the Cd accumulation was more abundant in the kidney than in the other organs and tissues. Together, distribution patterns of Mn, Fe, Cu and Cd in the liver and kidney of small Indian mongoose population from Hawaii were similar to mongooses from Japan as well as other terrestrial and marine mammals.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, an avian species, the great cormorant (Phalacrocorax carboalso) had higher Cu levels in the liver compared with other organs (Nam et al, 2005). Similarly, relatively higher concentrations of Mn in the liver have been shown in humans (Underwood, 1975;Wada, 1985), some wild terrestrial mammals (Lazarus et al, 2017), and marine mammals (Watanabe et al, 1996, Capelli et al, 2008, Agusa et al, 2011, and avian species (Nam et al, 2005, Horai et al, 2007.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…When comparing only females and males from the highly polluted areas, the females show 10.2-fold higher median Cd concentration in the livers and 7.4-fold higher concentration in the kidneys and 15.3-fold higher in the muscles. In an extensive study on four top European mammalian predators, Lazarus et al (2017) found that bears and wolf females also showed generally higher metal concentrations than males. The difference between the sexes may be due to the reasons suggested already above for lead.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rodents for risk assessment is a commonly accepted practise (Talmage and Walton 1991; Sawicka-Kapusta 1994, 1999; Sheffield et al 2001; Gdula-Argasińska et al 2004, 2005). In contrast, similar studies on top terrestrial carnivores are scarce, and only recently, an increasing interest in this topic can be observed (Millán et al 2008; Kalisinska et al 2012; Naccari et al 2013; Binkowski et al 2016; Lazarus et al 2017; Rodríguez-Jorquera et al 2017). The lack of data on large carnivores stems from the fact that in most European countries, they are protected by the Habitats Directive (Council Directive 92/43/EEC 1992) and Berne Convention (1979), and the availability of their tissues for studies is limited to two species, the red fox and golden jackal, whose populations are increasing (Arnold et al 2012) and the regulation of their populations by hunting is allowed in most of Europe.…”
Section: Introductionmentioning
confidence: 99%